Classification and petrogenesis of the Tongo dike-01 from the Tongo-Tongoma cluster, Sierra Leone: constraints from bulk rock geochemistry - Mathafeng, Katleho (Department of Geological Sciences, 2022)
The Man Craton in West Africa, like the Kaapvaal Craton in southern Africa, hosts diamondiferous kimberlites. However, West African kimberlites are commonly micaceous and unusual relative to archetypal South African kimberlites. Petrographically, they appear more similar to orangeites (aka Group II kimberlites), which represent a type of olivine-lamproite. A suite of 14 representative samples from the Cretaceous Tongo dike-01, Sierra Leone have been analysed for their bulk-rock major and trace elements as well as Sr-Nd-Pb isotope geochemistry. The primary objectives of this study are: 1) provide detailed petrographic observations of the dike, 2) classify the dike relative to kimberlites worldwide, 3) constrain the geochemical effects of secondary processes on bulk-rock analyses, 4) provide an estimate of the close-to-primary parent magma composition, and 5) constrain the petrogenesis of these diamondiferous rocks. The major element chemistry of the Tongo dike-01 reflects concentrations that are similar to both archetypal kimberlites and orangeites. Major elements such as SiO2 (~28.20 ± 3.90 wt. %) and CaO (~ 12.50 ± 1.80 wt. %) display archetypal kimberlite concentrations whereas Cr2O3 (~0.20 ± 0.01 wt. %) and P2O5 (~1.65 ± 0.60 wt. %) resemble those that define orangeites. The high abundance of phlogopite in this dike is illustrated by the high bulk-rock concentrations of K2O (~3.03 ± 0.50 wt. %) and Al2O3 (~4.08 ± 1.00 wt. %), similar to those of orangeites. Like the major element geochemistry, the trace element geochemistry of the Tongo dike-01 also displays mixed archetypal kimberlite and orangeite traits. Trace elements such as Nb (~365.0 ± 50.4 ppm) and Y (~18.77 ± 6.60 ppm) possess concentrations that are similar to kimberlites whereas Rb (~160.0 ± 14.8 ppm) and Th (~36.22 ± 5.30 ppm) resemble orangeites. Trace element ratios are no different, ratios such as Ce/Pb (16-82), Ba/Nb (1-8), La/Nb (0.6-1.2) and La/Sm (11-13) resemble those of kimberlites while La/Yb (280-520) are more similar to orangeites. However, unlike major and trace element geochemistry, the Sr-Nd-Pb isotope geochemistry of the Tongo dike-01 solely resembles those of archetypal kimberlites (87Sr/86Sr)i ~0,7039, (206Pb/204Pb)i ~18.88, (208Pb/204Pb)i ~40.02 and (143Nd/144Nd)i ~0.51253 ± 0.00001. Prior to interpretation of primary processes and parent magma composition estimates, the effects of secondary processes were first evaluated. These secondary processes include crustal contamination, ilmenite contamination and olivine entrainment/fractionation. Samples that had experienced these secondary processes were excluded and a suite of unaltered/least contaminated samples was compiled in order to constrain the close-to-primary magma composition of the Tongo dike-01 and interpret primary petrogenetic processes effecting the kimberlites. To determine a representative parent magma composition, a total of six out of the fourteen samples were excluded from consideration. The estimated close-to-primary magma composition for the Tongo dike-01 is suggested to be SiO2 ~28.20 ± 3.90 wt. %, Fe2O3 ~10.20 ± 1.70 wt. %, TiO2 ~1.70 ± 0.30 wt. %, Al2O3 ~4.08 ± 1.00 wt. %, K2O ~3.03 ± 0.50 wt. %, La ~363.12 ± 25.43 ppm, Gd ~15.87 ± 4.20 ppm, Yb ~1.020 ± 0.06 ppm, ( 87Sr/86Sr)i ~0.7039, ( 206Pb/204Pb)i ~18.88, ( 208Pb/204Pb)i ~40.02 and ( 143Nd/144Nd)i ~ 0.51253 ± 0.00001. Although the petrography and major element concentrations are similar to orangeites found in South Africa, the trace element and Sr-Nd-Pb isotope geochemistry of the Tongo dike-01 reflects a kimberlite composition. Thus, the Tongo dike-01 is more consistent with being classified as a relatively rare type of ‘mica-rich' kimberlite rather than orangeite. Kimberlites from around the world derive from the same asthenospheric mantle reservoir and their major element chemistry is controlled by the compositions/mineralogy of the lithospheric mantle assimilated during kimberlite evolution. The similarity of the trace element ratios and Sr-Nd-Pb isotopes of the Tongo dike-01 in this study relative to archetypal kimberlites worldwide strongly implies that the Tongo dike-01 derives from the same asthenospheric reservoir as these kimberlites, although mineralogically the Tongo dike-01 is different and has a different parent melt major element composition. This is interpreted to reflect the contribution of lithospheric mantle material that is mineralogically different to that assimilated by archetypal kimberlites during the ascent of the Tongo dike-01 parent magma through the sub-continental lithospheric mantle (SCLM). In the case of the Tongo dike-01, its primary melt is K2O-rich and must have assimilated more K2O-rich material in the SCLM. Such material is typically present as metasomatic products, e.g., Phlogopite-Ilmenite-Clinopyroxene (PIC) xenoliths observed in South Africa kimberlites. These xenoliths tend to possess abundant phlogopite. Thus, the main difference between the Tongo kimberlite and archetypal SA kimberlites is the fact that Tongo kimberlite assimilated more K2O-rich metasomatised material in the SCLM during its evolution.